ANALISIS PENGARUH TINGKAT RELIGIUSITAS, PENGETAHUAN DAN LINGKUNGAN SOSIAL TERHADAP MINAT MENABUNG MAHASISWA DI BANK SYARIAH KOTA MALANG (STUDI KASUS PADA MAHASISWA BANYUWANGI DI KOTA MALANG) - Nur’aini Ika Ramadhani; Jeni Susyanti; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABTRACKThis study aims to analyze the effect of the level of religiosity, knowledge and social environment on the interest in saving students in Malang city. This research was held in Malang city. The sampling technique used was simple random sampling technique. Respondents in this study were Banyuwangi students in Malang city with a total of 90 respondents from 927 students. This research is quantitative research and the method of data analysis used multiple linear regression. The results of this study indicated that partially the variable religiosity, knowledge has a significant effect on students 'interest in saving in Islamic banks, while the social environment variables have a positive and insignificant effect on students' interest in saving in Malang city Islamic banks. Simultaneously the variables of religiosity, knowledge and social environment have a significant effect on students' saving interest in Islamic banks at a significance level of less than 0.05 or 5%Keywords: level of religiosity, knowledge, social environment, interest in saving